Analysis Stability of Abutment on the Railway Bridge - -, Liliwarti; -, Silvianengsih; Candra, Febrian; -, Satwarnirat; Archenita, Dwina (International Journal of Advanced Science Computing and Engineering, 2022)
Railway bridge Bangunan Hikmah (BH 39) Pariaman (Padang– Pariaman Route) is a new bridge. This new bridge was built because the old one could not accommodate the load of the additional locomotive. The railway bridge consists of two parts: the upper structure and the substructure. The substructure consists of abutments and foundations. When the abutment accepts considerable lateral ground pressure, so the stability of the abutment will be disturbed. To resolve the problem, the need exists to study abutment reinforcement with geotextile or additional foundation pile to raise the stability abutments on the Railway bridge Bangunan Hikmah (BH 39) Pariaman. The result of the loading on the upper structure is obtained. The total vertical force acting on the abutment is 6111,624 kN, and the horizontal load is 2849,689 kN. Abutment stability analysis is carried out in 3 stages (without reinforcement, with reinforcement geotextiles, and with existence foundation pile (bored pile). The results of the analysis show value safety factor minimum without Reinforcement (SF) is 1,29; this shows that the abutment is unstable because the safety factor obtained is < 1.5,  with reinforcement geotextile, the value of the safety factor minimum  (SF) is 1,66,  this indicates that the abutment is stable but still critical and the value of the safety factor (SF) minimum with bored pile foundations is 2,10.  Installation of a bored pile foundation (pile group) at a depth of 10m shows a significant increase in the value of the safety factor. In the BH 39 Kurai Taji Pariaman railway bridge project, it is recommended to use a pile group foundation with a depth of 10 m.